1998
DOI: 10.2355/isijinternational.38.730
|View full text |Cite
|
Sign up to set email alerts
|

Solute Redistribution Model of Dendritic Solidification Considering Diffusion in Both the Liquid and Solid Phases.

Abstract: To estimate micro-segregation with dendritic solidification, a common method using an integral profile method has been developed. We considered three cases; (1 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…2) Thereafter, almost all microsegregation models incorporated the back diffusion. 21,22) It is easily understood that the change in diffusivity in the solid phase modifies the extent of microsegregation as well. Some studies showed that the SMF inhibited diffusivity in alloys.…”
Section: Resultsmentioning
confidence: 99%
“…2) Thereafter, almost all microsegregation models incorporated the back diffusion. 21,22) It is easily understood that the change in diffusivity in the solid phase modifies the extent of microsegregation as well. Some studies showed that the SMF inhibited diffusivity in alloys.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] For example, the thermal-driven buoyancy flow (also called natural convection, thermal convection or non-isothermal flow in some papers) in tundish and ladle with large volume capacity of liquid steel has been widely studied. [11][12][13][14] It is thought that non-isothermal flow has an obvious influence on the temperature distribution and inclusion removal in tundish and ladle.…”
Section: Introductionmentioning
confidence: 99%
“…Several models have been proposed for the case in which the liquid is completely mixed and finite diffusion works in the solid. [3][4][5][6][7][8] In Wołczyński's method 9,10) for back-diffusion phenomenon during the crystal growth the mass balance problem at the solid-liquid interface is separately treated from the solute redistribution in the solid. Therefore, by using this method, we can easily calculate the solidification path of a multicomponent alloy such as Fe-C-X alloy.…”
Section: Introductionmentioning
confidence: 99%